Mechanical Characterization of Polyurethane Elastomers: For Retrofitting Application against Blast Effects - Somarathna, H.M.C.C.; Raman, S.N.; Badri, K.H.; Mutalib, A.A. (Third Conference on Smart Monitoring, Assessment And Rehabilitation of Civil Structures, 2015)
In recent years, structural and materials engineers have focused their attention to develop feasible, constructible and cost effective retrofitting techniques to enhance the structural capacity and to minimize the damage due to impulsive loadings such as blast and impact. In this aspect, elastomeric polymers offer a unique proposition as retrofitting material for civil infrastructures, due to their attractive characteristics and morphology such as high elongation and energy absorption capacity. However, comprehensive understanding and proper evaluation of their characteristics and behavior are vital prior to developing a feasible retrofitting technique based on these materials. This paper discusses on the findings of experimental investigations undertaken to evaluate the mechanical properties under uniaxial tensile loading of selected types of palm-oil based polyurethane which were prepared by varying the chain extender (Polyethylene glycol, PEG), for it to be utilized as a retrofitting coating material on reinforced concrete structures, to enhance their resistance to blast effects. It was found that the properties of polyurethane elastomer are within the desired range and there is a higher possibility to apply the material as a sustainable and feasible retrofitting application for reinforced concrete structures under impulsive loadings.